The Pauline effect: the use of the Pauline epistles by early Christian writers - Strawbridge, J (De Gruyter, 2015)
This study offers a fresh approach to reception historical studies of New Testament texts, guided by a methodology introduced by ancient historians who study Graeco-Roman educational texts. In the course of six chapters, the author identifies and examines the most representative Pauline texts within writings of the ante-Nicene period: 1Cor 2, Eph 6, 1Cor 15, and Col 1. The identification of these most widely cited Pauline texts, based on a comprehensive database which serves as an appendix to this work, allows the study to engage both in exegetical and historical approaches to each pericope while at the same time drawing conclusions about the theological tendencies and dominant themes reflected in each. Engaging a wide range of primary texts, it demonstrates that just as there is no singular way that each Pauline text was adapted and used by early Christian writers, so there is no homogeneous view of early Christian interpretation and the way Scripture informed their writings, theology, and ultimately identity as Christian.